Differences in the endocannabinoid system of sperm from fertile and infertile men. - Sheena E M Lewis; Cinzia Rapino; Monia Di Tommaso; Mariangela Pucci; Natalia Battista; Rita Paro; Luke Simon; Deborah Lutton; Mauro Maccarrone (PLoS ONE, 2012)
Male infertility is a major cause of problems for many couples in conceiving a child. Recently, lifestyle pastimes such as alcohol, tobacco and marijuana have been shown to have further negative effects on male reproduction. The endocannabinoid system (ECS), mainly through the action of anandamide (AEA) and 2-arachidonoylglycerol (2-AG) at cannabinoid (CB(1), CB(2)) and vanilloid (TRPV1) receptors, plays a crucial role in controlling functionality of sperm, with a clear impact on male reproductive potential. Here, sperm from fertile and infertile men were used to investigate content (through LC-ESI-MS), mRNA (through quantitative RT-PCR), protein (through Western Blotting and ELISA) expression, and functionality (through activity and binding assays) of the main metabolic enzymes of AEA and 2-AG (NAPE-PLD and FAAH, for AEA; DAGL and MAGL for 2-AG), as well as of their binding receptors CB(1), CB(2) and TRPV1. Our findings show a marked reduction of AEA and 2-AG content in infertile seminal plasma, paralleled by increased degradation: biosynthesis ratios of both substances in sperm from infertile versus fertile men. In addition, TRPV1 binding was detected in fertile sperm but was undetectable in infertile sperm, whereas that of CB(1) and CB(2) receptors was not statistically different in the two groups. In conclusion, this study identified unprecedented alterations of the ECS in infertile sperm, that might impact on capacitation and acrosome reaction, and hence fertilization outcomes. These alterations might also point to new biomarkers to determine male reproductive defects, and identify distinct ECS elements as novel targets for therapeutic exploitation of ECS-oriented drugs to treat male fertility problems.